The Role of the Physical Environment in Promoting Physical Activity in Children Across Different Group Compositions. (November 2014) - Larson, Tracy A.; Normand, Matthew P.; Morley, Allison J.; Hustyi, Kristin M.
Physical activity is an important health-related behavior, but the environmental variables that promote or abate it are not well understood. The purpose of this study was to conduct a functional analysis evaluating the effect of the physical environment on moderate-to-vigorous physical activity (MVPA) in preschool children, and to evaluate the utility of the methodology across different group compositions. The Observational System for Recording Physical Activity in Children was used to define the test conditions and the measures of physical activity for eight preschool children. The functional analysis was implemented according to a multi-element experimental design. The highest levels of MVPA were observed when fixed playground equipment was available and at least one peer was present. Moreover, differential responding was observed across group compositions. The implications of this methodology and these findings on the development of interventions to increase MVPA are discussed.